RELATIONSHIP MOTIVATION WITH INTERDIALITYC WEIGHT GAIN (IDWG) CHANGES IN CHRONIC KIDNEY DISEASE PATIENTS - lutfi wahyuni; Ima Rahmawati; Moch Achwandi (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Chronic kidney disease is a failure of kidney function to maintain metabolism, and balance of fluid and electrolytes due to the progressive destruction of kidney structure. Increased fluid volume must be limited. If there is excess can cause edema, tightness and decreased consciousness. Therefore, patient motivation is needed to control changes of Interdialytic Weight Gain (IDWG). The aim of this study is to prove the relationship of patient motivation with changes of IDWG in CKD patients. The design of this study was correlational analysis with a cross-sectional approach. The sampling technique used non-probability sampling type purposive sampling, 40 CKD patients undergoing hemodialysis therapy at the RSUD Bangil were enrolled in this study. Data collection was using a questionnaire. Data analysis was using Spearman rho statistical test, which showed a significance value of 0,000 that was smaller than alpha (0.05), so it can be concluded that there was a significant relationship between patient motivation and IDWG changes of CKD patients undergoing hemodialysis therapy. Strong motivation to undergo hemodialysis is important because hemodialysis has become a necessity for him, a treatment must be undertaken by patients with chronic kidney disease.